Signaling network in phosphate starvation response and arbuscular mycorrhiza symbiosis in plants - Gu Mian, Nanjing Agricultural University, Nanjing (China),State Key Laboratory of Crop Genetics and Germplasm Enhancement; Chen Aiqun, Nanjing Agricultural University, Nanjing (China),State Key Laboratory of Crop Genetics and Germplasm Enhancement; Xu Guohua, Nanjing Agricultural University, Nanjing (China),State Key Laboratory of Crop Genetics and Germplasm Enhancement (Nanjing nongye daxue xuebao, 2012)
磷是植物生长发育的主要限制因子之一,主要以无机正磷酸盐的形态被植物吸收,而其在土壤中的移动性和生物有效性很低。为了适应磷缺乏的环境,植物进化出了包括与丛枝菌根真菌形成互惠共生体系在内的一系列适应性机制以增强对磷的吸收、转运和再利用等。所有的这些机制均是由复杂而精巧的分子调控网络控制的。近年来众多基因被鉴定并进行功能研究后与该调控网络联系起来,这些基因包括各种蛋白质基因和非编码RNA基因。本文旨在对当前该领域的研究进展作一总结,同时探讨植物缺磷与菌根信号转导途径间可能存在的相互关系。 Phosphorus （P）is one of the major limiting factors for plant growth and development. The accessible form of P to plants is inorganic phosphate （Pi）, the mobility and bioavailability of which is fairly low in the soft. In order to counteract the Pi deficient envi- ronment, plants have evolved an array of adaptive strategies, including forming mutualistie symbiotic associations with arbuseular my- corrhiza （AM） fungi, to enhance Pi uptake, translocation, and reutilization. All the strategies are fine tuned by a complex and elaborate molecular regulatory network,in which a large subset of protein-encoding genes and non-coding RNA genes are involved. Here, we review the current advances on this subject, and discuss the potential cross-talk between Pi starvation and AM symbi